Media Edukasi Komplementer Mengatasi Anemia Pada Ibu Hamil Di Puskesmas Kotabaru - Siti Zaitun; Hartinah Hartinah; Ika Friscila (Jurnal Pengabdian Bidang Kesehatan, 2024)
The mother's condition during pregnancy, childbirth, the postpartum period, and the baby being born are greatly influenced by the mother's health. The consequences of anemia in pregnant women include the risk of abortion, premature birth, fetal growth restrictions, increased risk of infection, low birth weight babies, as well as other complications such as difficulties during delivery, congenital abnormalities, and the risk of shock during the birth process. Complementary therapies refer to various systems of medicine and health care that are not included in conventional medicine. This therapy aims to complement conventional medical treatment and must be in accordance with applicable health values and laws. The aim of the activity is to create complementary educational media to overcome anemia in pregnant women at the Kotabaru Community Health Center. Activities will be carried out in January 2024 involving pregnant women and the community in the Kotabaru Community Health Center working area. The result is that activities have been carried out by providing education using poster media. Complementary implementation can be continued to inform the public so that pregnant women can be independent in maintaining their pregnancy and also have support from health workers and the community.